The Future Digitalisation of the Malaysian Employers Federation - Nasiruddin, Ismail (2025)
Technological changes have significantly become crucial for an organisation to remain relevant and competitive in the progressing world. This study investigates the future usage of technology and digitalisation of the Malaysian Employers Federation (MEF). The Malaysian Employers Federation (MEF) is a non-profit organisation practising harmonious Industrial Relations (IR) or Human Resources (HR) audit that represents the interests of employers in Malaysia. In recent years, the MEF has acknowledged the importance of technology in enhancing productivity and competitiveness. Despite this, MEF needs to remain relevant, visible, progressing and maintain its future existence by engaging with the digital world competitively. 8 informants from stakeholders were selected, which involved MEF director, and stake holders were selected as informants including government officials. Based on the literature review this organization faces various challenges and obstacles such as communication, efficiency, and training effectiveness. In recent years, the MEF has acknowledged the importance of technology in enhancing productivity and competitiveness. Despite this, MEF needs to remain relevant, visible, progressing and maintain its future existence by engaging with the digital world competitively. It is necessary for MEF to create or upgrade an effective management technology system (MTS) that could assist its members by timely supplying them with updated information, expertise, research, guidance, and other pertinent activities. This study has also discovered obstacles relating to the growth of the industry. Unstructured and semi-structured questions were asked of the informants who participated in these in-depth interviews. Information collected from interviews and in-depth observations was taken through mnemonic writing and analysed. The results of the study have been organized according to basic themes, organizational themes and global themes. In conclusion, this study has summarized a qualitative phenomenon about the MEF and its contribution to the country's economic growth. The analysis's findings indicate that the respondents have shown positive feedback with an attitude that leads to higher intentions to utilise digital technology on the current system.